Evaluation of Bank Soundness using the Risk Profile Method, Sharia Governance, Operating Profit, and Capital at Islamic Commercial Banks - Nabila, Annisa; Iryani, Lia Dahlia; Widyowati, Mutiara Puspa (Journal of Islamic Contemporary Accounting and Business, 2024)
The aim of this research is to assess the health level of Islamic Banks listed on the Indonesia Stock Exchange, utilizing the risk profile, Sharia governance, profitability, and capital method. Purposive sampling with specific criteria was employed as the sampling technique. The findings indicate that using the RGEC method, it predicts that two Islamic banks assessed are in a healthy condition. In 2019, Bank Panin Dubai Syariah achieved a composite score of 82.85%, categorized as healthy. In 2020, it obtained a composite score of 80%, maintaining a healthy category, and in 2021, it secured a composite score of 80%, sustaining a healthy categorization. As for Bank Syariah Indonesia, it is consistently deemed in very healthy condition. In 2019, it obtained a composite score of 91.42%, signifying excellent health. In 2020, it achieved a composite score of 94.28%, maintaining its very healthy status, and in 2021, it attained a composite score of 97.14%, indicating sustained excellent health.